Sustainable Certification for Future Generations: The Case of Family Business. (September 2014) - Delmas, Magali A.; Gergaud, Olivier
Business sustainability has been defined as meeting current needs while providing the ability of future generations to meet their own needs. However, few firms invest in practices geared at sustainability. In this article, we investigate how family ties to future generations via the intention of transgenerational succession can be associated with the adoption of sustainable practices. Using data from 281 wineries in the United States collected through a survey questionnaire, we show that ties to future generations, measured as the intention of the winery owner to pass down the winery to their children, are associated with the adoption of sustainable certification.